Neurochemical characterization of brainstem pro-opiomelanocortin cells - Georgescu, Teodora (2020)
Genetic research has revealed pro-opiomelanocortin (POMC) to be a fundamental regulator of energy balance and body weight in mammals. Within the brain, POMC is primarily expressed in the arcuate nucleus of the hypothalamus (ARC), while a smaller population exists in the brainstem nucleus of the solitary tract (POMCNTS). We performed a neurochemical characterization of this understudied population of POMC cells using transgenic mice expressing green fluorescent protein (eGFP) under the control of a POMC promoter/enhancer (PomceGFP). Expression of endogenous Pomc mRNA in the nucleus of the solitary tract (NTS) PomceGFP cells was confirmed using fluorescence-activating cell sorting (FACS) followed by quantitative PCR. In situ hybridization histochemistry of endogenous Pomc mRNA and immunohistochemical analysis of eGFP revealed that POMC is primarily localized within the caudal NTS. Neurochemical analysis indicated that POMCNTS is not co-expressed with tyrosine hydroxylase (TH), glucagon-like peptide 1 (GLP-1), cholecystokinin (CCK), brain-derived neurotrophic factor (BDNF), nesfatin, nitric oxide synthase 1 (nNOS), seipin, or choline acetyltransferase (ChAT) cells, whereas 100% of POMCNTS is co-expressed with transcription factor paired-like homeobox2b (Phox2b). We observed that 20% of POMCNTS cells express receptors for adipocyte hormone leptin (LepRbs) using a PomceGFP:LepRbCre:tdTOM double-reporter line. Elevations in endogenous or exogenous leptin levels increased the in vivo activity (c-FOS) of a small subset of POMCNTS cells. Using ex vivo slice electrophysiology, we observed that this effect of leptin on POMCNTS cell activity is postsynaptic. These findings reveal that a subset of POMCNTS cells are responsive to both changes in energy status and the adipocyte hormone leptin, findings of relevance to the neurobiology of obesity.